Faktor-faktor yang Berhubungan dengan Deteksi Dini Kanker Payudara (SADARI) pada Siswi di MAN 3 Palembang Tahun 2024 - Putri, Mirta Dwi; Rahmawati, Eka; Dhamayanti, Reffi (Universitas Batanghari Jambi, 2025)
This study aims to determine the relationship between knowledge, attitudes and sources of information with Early Detection of Breast Cancer (SADARI) in female students at MAN 3 Palembang in 2024. The research method used in this study is quantitative research using an analytical survey with a cross-sectional approach with a population of 165 infant students with a sample of 62 using a non-random sampling method. Data analysis used the Chi Square statistical test. The results of this study revealed that there was a significant relationship between knowledge, attitudes and sources of information with the incidence of early detection of breast self-examination (SADARI) in MAN 3 Palembang in 2024.